Effect of priming on seed germination attributes of pansy (Viola x Wittrockiana) under laboratory conditions - RISHU SHARMA; B.S. DILTA; H.S. BAWEJA; B.P. SHARMA (Seed Research, 2026)
Pansy (Viola x Wittrockiana Gams.) is a very important bedding plant and widely grown as a winter annual in India. The poor and slow rate of seed germination is a major problem in pansy; its seeds are very costly especially the F, hybrids. Therefore, seed germination studies were carried out in pansy seeds with polyethylene glycol (PEG-6000) @300 g/l, GA,3 @20 mg/l, biopriming with Trichoderma viridi @ 8 g/kg of the seed, hydropriming (with water) and control (non-primed) for two consecutive years (2010 and 2011). The germination percentage increased tremendously in both the years of study with all the priming treatments in comparison to non-primed seeds and can also be evidenced by pooled analyses of the two years data. Among all the priming treatments, GA3@20 mg/1 had recorded the highest results w.r.t. germination percentage (93.12%), seedling length (6.55 cm), seedling vigour index (609.6), seedling fresh weight (15.80 mg), seedling dry weight (1.50 mg). The lowest germination percentage (60.75%), seedling length (3.15 cm), seedling vigour index (195.3), seedling fresh weight (10.30 mg), seedling dry weight (0.78 mg) recorded in non-primed or control seeds. The minimum seedling moisture content (91.20%) was recorded in PEG-6000 @300 g/l and maximum seedling moisture content (94.85%) was recorded in non-primed or control seeds.